Germination and field emergence of vegetable seeds in composted biosludge - Francis, Connie. (Universiti Malaysia Sarawak (UNIMAS), 2004)
A field study was conducted to detennine the influence of composted biosludge on seed gennination and seedling emergence of ten types of vegetables. Results revealed apparent improvement on the percentage gennination and emergence of vegetable seedlings for both composted-soil (2 compost:1 topsoil (C2SI» and (l compost:1 topsoil (CIS I»compared to non-composted soil (control (CoSd) for all types of vegetable. Early gennination and emergence have also observed for treatments C2S1 and CIS I for A. blilum, Brassica spp., Ipomoea aquatica, L. esculentum, P. erosus and R. sativus. Gennination and emergence ofA. blitum, B. rapa, A. esculentus, L. esculentum and R. sativus was highest in C2SI. Both C2S1 and CISI did not contribute marked difference on the percentage of gennination and emergence of seedlings for I. aquatica, P. vulgaris, P. erosus and R. sativus. The biomass exhibited evidence of high and vigorous seedlings growth occurred for C2S I followed by CISI. hence concluded the advantage ofdressing topsoil with composted biosludge.